Cuba eliminates mother-to-child transmission of HIV and congenital syphilis: a call to action for the Americas Region - Kamb, Mary L.; Caffé, Sonja; Perez, Freddy; Bolan, Gail; Ghidinelli, Massimo N. (Brazilian Journal of Sexually Transmitted Diseases, 2022)
On June 30, 2015, the World Health Organization (WHO) validated Cuba as the first country in the world to eliminate mother-to-child transmission of HIV and congenital syphilis as public health problems. What makes this achievement especially laudable is that Cuba is a nation with limited economic resources. With an estimated Gross Domestic Product (GDP) of USD 9,900 (2010), Cuba ranks 114th of 230 nations on this global economic indicator(1).